Breathwork and holistic wellbeing: A protocol for a scoping review - Beauchamp, Fern Eleanor; Bispo, Emily; Galinha, Iolanda Costa; Kemp, Andrew H. (PloS one, 2025)
Breathwork has great potential for supporting connections to self, others, and nature, laying the foundations for individual, collective, and planetary wellbeing. While reviews have summarised the impacts of a wide range of breathwork techniques on outcomes relating to individual wellbeing, past work has neglected broader contexts. Here we present a protocol for a scoping review to identify and summarise the available literature relating to a broader range of wellbeing domains, focused on connection to self (individual wellbeing), others (collective wellbeing), and nature (planetary wellbeing). In synthesising the literature, we will determine how and when holistic wellbeing might arise through breathing interventions. Guided by standardised guidelines for conducting scoping reviews, six electronic databases (PubMed, Scopus, Web of Science, APAPsycArticles, Psychology and Behavioural Sciences Collection and Cochrane), grey literature and reference lists of included literature will be searched. Using the Rayyan platform, two reviewers will independently screen title/abstracts after which the full texts of relevant articles will be reviewed based on predetermined criteria. Study details, breathing intervention type and wellbeing outcomes relevant to the research question(s) will be extracted. Numerical analysis of data items and descriptive qualitative analysis of data across the three domains will be reported. Preliminary results will be shared with breathwork facilitators, and their feedback will help highlight gaps not explored in the literature and to refine discussion of the findings in an applied context. We hope that results will inform subsequent research and encourage deeper reflection on the role of breathwork across wider contexts. This research will contribute to the growing evidence base for promoting the inner development of individuals and communities focused on major societal challenges.